Trading Between India and China and its Effect on COVID – 19: Exploring Trade Relations and Financial Competition between India and China amidst the COVID-19 Epidemic (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The COVID-19 epidemic has had an effect on trade, assisting soft power movements. Theresearch concentrates on trade relations between India and China by presenting a historical foundation oftrade developments between the two nations and briefly discussing their trade philosophies. It also tries tokeep track of commercial transactions with India and China during the epidemic. It examines whether Indiacould compete financially with China by refusing to trade with it, or whether the CHINDIA approach wouldbe more advantageous. The study also emphasises India's reliance on China for medical supplies,arguing that a governed trade cooperation with China would be financially viable to India.